2016
DOI: 10.1152/jn.00995.2015
|View full text |Cite
|
Sign up to set email alerts
|

Network burst activity in hippocampal neuronal cultures: the role of synaptic and intrinsic currents

Abstract: AK, Marks JD, van Drongelen W. Network burst activity in hippocampal neuronal cultures: the role of synaptic and intrinsic currents. J Neurophysiol 115: 3073-3089, 2016. First published March 16, 2016 doi:10.1152/jn.00995.2015.-The goal of this work was to define the contributions of intrinsic and synaptic mechanisms toward spontaneous network-wide bursting activity, observed in dissociated rat hippocampal cell cultures. This network behavior is typically characterized by short-duration bursts, separated by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 65 publications
13
48
1
Order By: Relevance
“…To test this, we pharmacologically blocked either AMPARs or NMDARs and compared the effect on control and KS neuronal network activity at DIV 28. In accordance with previous work 30,31 , we found in our control networks that acute treatment with an AMPAR antagonist (NBQX, 50 µM) abolished all network burst activity, whereas inhibiting NMDARs (D-AP5, 60 µM) only slightly decreased the network burst activity ( Fig. 4A, C).…”
Section: Increased Sensitivity To Nmda Receptor Antagonists In Ks Patsupporting
confidence: 93%
See 1 more Smart Citation
“…To test this, we pharmacologically blocked either AMPARs or NMDARs and compared the effect on control and KS neuronal network activity at DIV 28. In accordance with previous work 30,31 , we found in our control networks that acute treatment with an AMPAR antagonist (NBQX, 50 µM) abolished all network burst activity, whereas inhibiting NMDARs (D-AP5, 60 µM) only slightly decreased the network burst activity ( Fig. 4A, C).…”
Section: Increased Sensitivity To Nmda Receptor Antagonists In Ks Patsupporting
confidence: 93%
“…Previous studies on rodent-derived neuronal networks have shown that burst duration is directly influenced by AMPARs and NMDA receptors (NMDARs). Specifically, previous reports used receptor-type specific antagonists to show that AMPAR-driven bursts have short durations while NMDAR-driven bursts have comparatively longer durations 30 . We therefore hypothesized that increased NMDAR activity contributed to the lengthened bursts seen in KS networks.…”
Section: Increased Sensitivity To Nmda Receptor Antagonists In Ks Patmentioning
confidence: 99%
“…The blockade of GABA currents has previously been shown to not prevent the firing of NBs in cell culture networks [35,36,37]. Compared with the results in control conditions (i.e., unblocked GABA; “GABA-ON”), the blockade of inhibitory synapses in the model (GABA-OFF) caused an increase in the MFR, MBR, MFIB and a decrease in the MBD, both in our recordings and in simulations (Fig 3D; for further details see S5 Appendix).…”
Section: Resultsmentioning
confidence: 99%
“…In general, hyperactivity in networks can be mediated by two major factors: a) changes in synaptic signaling between neurons resulting in altered E/I-balance; and b) changes in intrinsic electrophysiological properties of the neurons within the networks resulting e.g. in hyperexcitability (38). At the single cell level, we found in SMARCB1-, MLL3-and MBD5-deficient cultures a strong reduction in both excitatory and inhibitory synaptic inputs.…”
Section: Kss Gene-deficient Network Share a Common Mode Of Failurementioning
confidence: 73%